Teknik Relaksasi untuk Menurunkan Kecemasan Pada Ibu Hamil di Wilayah Puskesmas Pakualaman - Shinta Adella; Alfi Purnamasari (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of group therapy conducted in this research was to determine the effect of relaxation technique to reduce anxiety in pregnant women within the working area of Pakualaman Community Health Center. The research subjects consisted of seven pregnant women who experienced anxiety disorder in the moderate category. The methods for data collection were observation, interview, and focus group discussion, as well as a pre-test using a pregnancy anxiety scale with the results of Cronbach a = 0.896 at 28 items and reliability of 0.896. Data analysis techniques were carried out qualitatively based on the results of the therapy process and quantitatively by conducting a post-test. The research results revealed a decrease in anxiety, both qualitatively and quantitatively. The qualitative results showed that the research subjects were able to feel more positive, calmer, and more comfortable during their pregnancy and being optimistic when they were about to face the delivery process, which affected the perceived behavior such as reduced dizziness and comfortable sleep. Meanwhile, the quantitative results showed a decrease in score and the level of anxiety experienced by the research subjects between before and after participating in the group therapy process with the value of z = -2.366 with a significance of p = 0.018 (p <0.05). Thus, it can be concluded that group therapy with relaxation technique could reduce anxiety in pregnant women within the working area of Pakualaman Community Health Center.